What can multiple causes of death tell about cardiovascular mortality during COVID-19 pandemic in the United States - Ukolova, Elizaveta; Burcin, Boris (Journal of public health, 2024)
BACKGROUND: The COVID-19 pandemic may have caused an underestimation of cardiovascular disease (CVD) mortality, as COVID-19 was predominantly recorded as the underlying cause of death. This study investigates CVD-related excess mortality and recording of CVD on the death certificates during 2020-2021, considering underlying (underlying causes of death (UCD)), immediate and contributory causes. METHODS: We utilize US Multiple-Cause-of-Death Mortality Data. Excess deaths are assessed by comparing actual 2020-2021 deaths with Seasonal Autoregressive Integrated Moving Average model predictions. To understand changes in cause-of-death recording, we use the standardized ratio of multiple to underlying causes (SRMU). RESULTS: Excess CVD mortality is most prominent in contributory causes, including hypertensive disease, essential hypertension, and acute myocardial infarction. While excess of contributory CVDs generally decreased in 2021, acute myocardial infarction, pulmonary heart diseases and other circulatory diseases showed a continual increase. Changes in SRMU from 2020 to 2021, compared to 2010-2019, reveal shifts in coding practices, particularly for pulmonary heart, cerebrovascular diseases, non-rheumatic valve disorders and heart failure. CONCLUSIONS: The COVID-19 pandemic has significantly increased CVD-related mortality, which is not fully captured in conventional analyses based solely on the UCD. The trend of coding CVDs as non-underlying causes of death accelerated during 2020-2021. Multiple-causes-of-death should be employed to evaluate mortality when new leading cause of death emerges.
Keywords: Cause of Death; pandemie; kauzalita; COVID-19; kardiovaskulární nemoci; Pandemics; mortalita; Spojené státy americké; příčina smrti; Humans; Cardiovascular Diseases; lidé; Causality; infarkt myokardu; Myocardial Infarction; United States; Mortality